KONFLIK BATIN TOKOH UTAMA NOVEL PUDARNYA PESONA CLEOPATRA KARYA HABIBURRAHMAN EL SHIRAZY - Lisa Anggraini; Novia Juita; Hamidin Hamidin (Faculty of Languages and Arts, Universitas Negeri Padang, 2013)
The research purpose of decribe about the inner conflict of the main character in the novel Pudarnya Pesona Cleopatra by Habiburrahman El Shirazy review of aspects of the id, ego, and superego in accordance with the theory states that by Sigmund Freud. Step of the research was conducted to: 1) read a novel and to know the contents of the novel, 2) find the main of character, 3) symbol of exspression or utterance make the main character who is assumed about the inner conflict. The techniques of data analysis doing by: 1) choose of the inner conflict of the main character to aspect of the id, ego, and superego, 2) the interpretations of the data, 3) the formulate of conclusions and resultof the research. The result of the research talk about the aspect id, ego, and superego the main of character “Aku” and Niyala in the novel to happen inner conflict. The inner conflict they are to happen reflected the events that happened. The inner conflict event influenced by aspek id,ego, and superego inner conflict the main character “Aku” is more concerned with statisfying the id with ego. Superego functioning resulting in only little. In the figure Niyala to happen balance between aspect of the id,ego, and superego.